2019
DOI: 10.1002/mma.5610
|View full text |Cite
|
Sign up to set email alerts
|

Global existence of smooth solution to 2D relativistic membrane equation in asymptotically flat FLRW space‐time

Abstract: This paper is concerned with the 2D relativistic membrane equation evolving in curved space‐time, whose metric is prescribed as a small perturbation to the flat Friedmann‐Lemaître‐Robertson‐Walker (FLRW) metric with time‐dependent coefficients. Thanks to the partial “null structure” of the membrane equation and the properties of the background metric, we could prove the global stability of a class of time‐dependent solutions by weighted energy estimate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Fortunately, these borderline terms exhibit linearizable feature. Therefore, motivated by [13] (see also [29,[40][41][42]), we resolve these difficulties by the method of linearization and hierarchies of energy estimates. In particular, we use the L ∞ − L ∞ estimate for the KG equation [27] in the procedure of linearization.…”
Section: The Ekg Systemmentioning
confidence: 99%
“…Fortunately, these borderline terms exhibit linearizable feature. Therefore, motivated by [13] (see also [29,[40][41][42]), we resolve these difficulties by the method of linearization and hierarchies of energy estimates. In particular, we use the L ∞ − L ∞ estimate for the KG equation [27] in the procedure of linearization.…”
Section: The Ekg Systemmentioning
confidence: 99%
“…Luo and Wei [19] proved the global existence of smooth solutions to 2D isentropic Chaplygin gases without vorticity in curved space when the initial data is small and has compact support. Recently, in order to investigate the influence of the background metric to the stability of the large solution of relativistic membrane equations, Wei [24] studied a class of time-dependent Lorentzian metric and showed that when the decay rate of the derivative of the given metric is larger than 3/2, then a class of time-dependent large solution to the relativistic membrane is globally stable, while, therein, the highest-order energy is still growing with respect to time.…”
Section: Background Materials and Outline Of This Papermentioning
confidence: 99%